2015
DOI: 10.2106/jbjs.m.01189
|View full text |Cite
|
Sign up to set email alerts
|

International Health Electives in Orthopaedic Surgery Residency Training

Abstract: A minority of the orthopaedic surgery residency programs that participated in this study offers international health elective opportunities to trainees. Barriers such as time parameters and funding limit their availability. Our results characterize international health electives and highlight potential areas of intervention that could increase their availability to a greater number of residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 20 publications
3
34
0
Order By: Relevance
“…Ophthalmology residents 58 2012 54% of ophthalmology residency program survey respondents offered GH electives. Orthopedic residents 59,60 2014, 2015 26% of orthopedic residency program survey respondents offered GH electives. Otolaryngology residents 61 2010 23% of US otolaryngology departments identified GH initiatives within their departments; 90% of those initiatives supported resident involvement.…”
Section: Graduate Medical Educationmentioning
confidence: 99%
“…Ophthalmology residents 58 2012 54% of ophthalmology residency program survey respondents offered GH electives. Orthopedic residents 59,60 2014, 2015 26% of orthopedic residency program survey respondents offered GH electives. Otolaryngology residents 61 2010 23% of US otolaryngology departments identified GH initiatives within their departments; 90% of those initiatives supported resident involvement.…”
Section: Graduate Medical Educationmentioning
confidence: 99%
“…The barriers are multimodal, including home residency logistics, funding, accreditation board approval, and ethical implications. 7,12,14,21,22 Our survey results demonstrated that there are barriers regarding funding and ACGME approval. A high percentage of residents (47.7% [71/149]) responded that they were unwilling to pay out of pocket for international rotations.…”
Section: Barriersmentioning
confidence: 87%
“…A 2014 survey of residency programs showed that only 26% of residency programs have established opportunities for their trainees to rotate abroad. 11 However, whether this number of available international rotation meets the orthopedic resident demand remains unknown. The current study provides evidence that the majority of orthopedic residents show serious interest in rotating abroad and that this number may surpass the number of available opportunities to train internationally.…”
Section: Discussionmentioning
confidence: 99%
“…According to a national survey done in 2014, only 26% of orthopedic residency programs offer international training opportunities. 11 The survey also hinted at growing interest among orthopedic residents. Previously, a study at the University of Washington indicated that 60% of orthopedic residents would be willing to enroll in an international health elective if given the opportunities.…”
mentioning
confidence: 99%